Kielletty kupoli, avattu alttari : Venäläisyyden häivyttäminen Suomen ortodoksisesta kirkkoarkkitehtuurista 1918 1939 - Kemppi, Hanna (Suomen Muinaismuistoyhdistys, 2017)
This dissertation examines the complex and sensitive issue of shaping a Finnish style for Orthodox church architecture in Finland in the interwar period 1918 1939. It is argued in the dissertation that the phenomenon of effacing the Russianness of Orthodox church architecture of Finland proceeded in two stages and, in its entirety, was more complex than previously assumed. Firstly, the dissertation explores the growing anti-Russian atmosphere during and shortly after the Civil War of 1918 and measures taken against unwanted Orthodox cultural heritage in Finland. In particular, the garrison churches of the Russian Imperial Army were explicated as disfiguring objects representing foreign influence in Finnish national culture that had to be cleaned away by eliminating them from the landscape. Secondly, the plans and realisation of creating a Karelian-Finnish style for Orthodox church architecture in the 1920s and 1930s are investigated, revealing designs commissioned from architect Veikko Kyander by the Orthodox Church of Finland. The research reconstructs the Orthodox church architecture of the period with the mapping of 21 churches and chapels built in Finland in the interwar years. The core actors in demarcating the Finnish style included not only church authorities but also antiquarian and state authorities. The analysis of the plans and realisation of the churches and chapels shows the significance of negative choice and the great impact of the building authorities in creating suitable de-Russified designs. It appears that the Finnish style was based on the eclecticism of contemporary Finnish architecture. The analysis of the new ascetic chapel interiors of the Border Karelia region reveals in concrete terms the poor financial situation of the congregations, but it also seems to imply a new uncluttered way of organising the interior. On the other hand, the interiors were based on ecclesiastical artefacts of Russian origin. There was thus a significant dichotomy between the foreign interior and the Finnish ...